PENDEKATAN PASTORAL KONSELING MELALUI TRADISI E”HAKA/E’HA: STRATEGI KOMUNITAS TALAUD DALAM PENCEGAHAN PENCURIAN DAN PEMULIHAN HUBUNGAN SOSIAL - Sapoh, Fani; Awalo, Merri Lusia; Baraa, Fony; Ratunguri, Isye (PT. Giat Konseling Nusantara, 2024)
The E'haka/E'ha tradition is a village rule in Talaud, North Sulawesi, dating back to 1935, to address coconut theft. For 3 months, people are prohibited from picking coconuts for commercial purposes, except for personal needs or special events. There are sanctions for violators, such as fines and public apology rituals. The implementation mechanism involves community leaders announcing the rules, a team of supervisors to monitor, and active participation from the community. Sanctions for violators include monetary fines, confession, and acts of atonement. In pastoral counseling, this tradition is used as an approach to help communities overcome conflict, restore relationships, and build solidarity. The functions of pastoral counseling include guiding in ethical decision-making, reconciliation, strengthening community solidarity, and spiritual growth. It helps maintain social harmony and prevent conflict within the community